Strength Analysis of Fiberglass Reinforced Sandwich Composites with Extruded Polystyrene Core - Tegar Arya Nusantara; Hendri Chandra; Ozkar F. Homzah (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2026)
The use of drones has rapidly increased across various sectors due to technological advancements and reduced production costs. One of their applications is transporting materials in hard-to-reach construction areas. Carbon fiber is commonly used for drone frames; however, it has drawbacks such as high cost, low impact resistance, and difficulty in recycling. This study investigates the potential of a sandwich composite material made from WR200 fiberglass and extruded polystyrene (XPS) foam core as a lightweight and economical alternative for drone frame manufacturing. Tensile testing (ASTM D638 Type 1) and bending testing (ASTM C393) were conducted to evaluate the material’s strength. The results showed the highest tensile strength of 131 MPa at a 40% fiber volume fraction, with a consistent increase in strength observed from 20% to 40% fiber volume. Bending tests also revealed strength improvement, reaching a maximum value of 47.80 MPa at 40% fiber volume, with an average maximum load of 585 N. The results from both tensile and bending tests indicate that the amount of E-glass fiber in the epoxy matrix significantly affects tensile and bending strength. As the fiber content increases, the strength improves as well; however, it also leads to increased stiffness.